Workers and New Technology? Analyzing the Complex and Multidimensional Relation through Job Quality - Refslund, Bjarke (Nordic Journal of Working Life Studies, 2025)
While the impact of new technology on work is vast, our knowledge remains somewhat fragmented, particularly from a workers’ perspective. This article applies job quality as a multi-dimensional approach to contribute to deepening our understanding of the effect new technology has for public sector workers in Denmark. Job quality is a multi-dimensional concept, and the technological development has a different impact on the various dimensions leading to somewhat mixed results. Despite studying different occupations, the impact on some dimensions was clearer: the results show how worker autonomy is challenged by new technology, the physical work environment is improved, and levels of workload, stress, and job intensity are being more negatively affected. Overall, new technology is improving some dimensions of job quality, worsening others, and yet other dimensions remain less affected, contributing to the overall complexity. However, there is a subjective dimension, with the same technology having varying impact on workers.